2021
DOI: 10.1371/journal.pcbi.1009684
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of NIPT aneuploidy detection software tools with clinically validated NIPT samples

Abstract: Non-invasive prenatal testing (NIPT) is a powerful screening method for fetal aneuploidy detection, relying on laboratory and computational analysis of cell-free DNA. Although several published computational NIPT analysis tools are available, no prior comprehensive, head-to-head accuracy comparison of the various tools has been published. Here, we compared the outcome accuracies obtained for clinically validated samples with five commonly used computational NIPT aneuploidy analysis tools (WisecondorX, NIPTeR, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…papers included as base for Additional file 1 : Table S1). A more detailed, scientific unbiased comparison of capabilities of different NIPT-platforms would be critical, as in the literature it is rarely addressed [ 20 ] or done [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…papers included as base for Additional file 1 : Table S1). A more detailed, scientific unbiased comparison of capabilities of different NIPT-platforms would be critical, as in the literature it is rarely addressed [ 20 ] or done [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Assay Software assessed the log likelihood ratio (LLR) for each target chromosome and each sample to provide a determinant of aneuploidy. The LLR is the probability of a sample being affected by the observed coverage versus the probability of a sample being unaffected given the same observed coverage [ 10 ]. Table 1 represents the high-risk of trisomy and high-risk LLR cut-offs of monosomy line for aneuploidies of clinical indication for NIPS by the Illumina VeriSeqTM NIPT assay software.…”
Section: Methodsmentioning
confidence: 99%
“…The copyright holder for this this version posted September 23, 2022. ; https://doi.org/10.1101/2022.09. 20.22280152 doi: medRxiv preprint [9]. Kucharik et al suggested that for MD NIPT assays, sequencing coverage should be 10-20M RPS, with the exact minimum coverage depending on the fetal DNA fraction and target region length [10].…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…Previous low-coverage WGS based NIPT studies have demonstrated that one of the most important factors of successful NIPT analysis is sequencing coverage (depth) [8]. For full chromosome aneuploidy detection, WisecondorX [8], for example, has shown to accurately operate with coverage of 5 million (M) reads per sample (RPS), while some other tools require coverage of 20M RPS to keep the number of false-negative trisomy calls under clinically acceptable 1% screening test limit [9]. The higher the sequencing coverage, the greater the likelihood of comprehensive and confident genome-wide interrogation and, therefore, more accurate evidence to infer chromosomal or even sub-chromosomal aberrations [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation